INVESTIGATION OF SLEEVE BEARING FAILURES IN API 610 BB3 PUMPS FOR WATER INJECTION APPLICATION - Machfud, Adam Aliyya; Kriswantoro, Yosep Joko; Nurrahman, Ardhi Febrian; Priambudi, Aris (International Journal of Mechanical Engineering Technologies and Applications, 2025)
The reliability of multistage centrifugal pumps, particularly API 610 BB3 types, is critical in water injection systems commonly used in oil and gas operations. This study aims to identify and analyze the dominant failure modes in sleeve bearings used in water injection pump applications, considering comprehensively existing design, operational, and maintenance aspects. The investigation covers analysis using not only equipment condition data (vibration, temperature, oil analysis) but also material examinations, such as optical microscopy, SEM (Scanning Electron Microscope), and EDS (Energy Dispersive Spectroscopy). The results indicate that the root cause of the sleeve bearing failure is lubrication failure, which is attributed to several contributing factors, including improper ISO Code settings for oil analysis and inadequate bearing temperature protection settings. Low-effort and high-impact improvements are proposed, including changing the lube oil type from mineral-based to synthetic-based, using lube oil with higher viscosity, adjusting the ISO Code for oil analysis, and modifying the bearing temperature protection settings. The results of this study are expected to provide a deeper understanding of the sleeve bearing failure mechanism and its implications for equipment reliability, serving as the basis for developing more effective mitigation strategies.